Technology Auctions as the Newest Component of Innovation Culture - Klimenko, K.S. (Science and Innovation, 2024)
The concept of innovation culture as a key element of innovative development of economy has been analyzed; its main components have been identified. Technology auctions as one of new tools for effective innovation have been considered. The basic idea of auctions and the main improvements caused by this type of communication between buyers and sellers of technologies have been determined. The necessity of such activities in Ukraine has been substantiated.